37 Use of antibiotics in deteriorating palliative patients – a retrospective analysis. (13th October 2019) - Page, Andrew; Rayment, Clare
Abstract : Background: In palliative care, 24–48hr antibiotic trials are prescribed in patients who have clinically changed and may be entering the last days of life(LDOL), but where infection is considered a possible reversible factor. Does this treatment benefit or burden patients? Aim: To determine the incidence of this in hospice practice, assess survival rates and identify common predictive factors of poor response. Method: Using SystmOne, a retrospective analysis of admissions to Marie Curie Hospice, Bradford Inpatient Unit between August-October 2018 was conducted. Data was collected for all inpatients starting antibiotics including diagnosis, OACC, details of antibiotic therapy, and admission outcome (discharge/death). Patients documented to be potentially entering LDOL when therapy was initiated were identified. Results: 78 patients were admitted, of which 40% (31/78)received antibiotics. Of those receiving antibiotics, 77% (24/31)had cancer and 25% (8/31)received multiple antibiotic courses. In 35% (11/31)cases, concerns the patient may be entering LDOL were documented when antibiotic therapy was initiated. Of these, 91% (10/11) died during the admission. Of those who died, all had cancer; the majority with metastatic disease(8/10), Karnofsky scores =40% (7/10), a 'Deteriorating'(5/10) or 'Unstable'(3/10) Phase of Illness and mean duration from antibiotic initiation to death was 5.4 days (range:1–12). In patients who received multiple antibiotic courses, 75%(6/8) died during admission. Discussion: Antibiotic use in this context appears relatively common and generally has a poor outcome, suggesting treatment could be an unnecessary burden for this patient group. Metastatic cancer, Karnofsky scores =40%, an 'Unstable' or 'Deteriorating' Phase of Illness and multiple antibiotics during admission may help predict a poor response.